2019
DOI: 10.1021/acsnano.9b08191
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensionally Free-Formable Graphene Foam with Designed Structures for Energy and Environmental Applications

Abstract: Three-dimensional assemblies of graphene have been considered as promising starting materials for many engineering, energy, and environmental applications due to its desirable mechanical properties, high specific area, and superior thermal and electrical transfer ability. However, little has been done to introduce designed shapes into scalable graphene assemblies. In this work, we show here a combination of conventional graphene growing technique–chemical vapor deposition with additive manufacturing. Such synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 49 publications
0
76
0
Order By: Relevance
“…Various oxides have the ability to act as substrates for growing few-layer graphitic or graphene under CVD conditions, such as MgO, 81 ZnO, 82 CaO, [83][84][85] SiO 2 , [86][87][88][89][90] and so forth. The oxides can prompt the decomposition of the carbon source and the deposition of graphitic carbon on their surface.…”
Section: Cvd On Oxide Templates For 3dgmentioning
confidence: 99%
See 1 more Smart Citation
“…Various oxides have the ability to act as substrates for growing few-layer graphitic or graphene under CVD conditions, such as MgO, 81 ZnO, 82 CaO, [83][84][85] SiO 2 , [86][87][88][89][90] and so forth. The oxides can prompt the decomposition of the carbon source and the deposition of graphitic carbon on their surface.…”
Section: Cvd On Oxide Templates For 3dgmentioning
confidence: 99%
“…89 Efforts have been made on fabricating graphene monoliths with a finer interconnected network. Xu et al 90 reported 3D free-formable graphene foams by combination of 3D printing and CVD (Figure 11H). Porous silica templates were prepared by digital light process method with photopolymerization of resin.…”
Section: Cvd On Oxide Templates For 3dgmentioning
confidence: 99%
“…Till now, various methods have been developed to prepare 3D graphene such as template-assisted methods, assembly of graphene oxide (GO), and laser-introduced methods. [8] Due to the difference in preparation methods, these 3D graphene have different structures at the macroscopic level such as powder, paper-like, and monolithic structures. [9] Compared with the powder and paper-like graphene, the monolithic graphene (such as graphene foam (GF) and graphene aerogel (GA)) have 3D structures at both micro-and macro-scale.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from thermal reduction and chemical reduction, CVD method is the other effective way in preparing carbon materials with few defects, rather than improving porous carbon to be more perfect. The carbon edge sites including functional groups and defects can be lowered to 4 at % [3d,6] . Among these three methods, thermal reduction and chemical reduction have more advantages when applied to mass production, while CVD is super in fine structure fabrication.…”
Section: Introductionmentioning
confidence: 99%